Against the multilingual turn as paradigm replacement: Reconsidering Kubota’s charge - Angelo Ria (De Gruyter, 2021)
In her 2016 paper, entitled, The Multi-Plural Turn, Post-Colonial Theory and Neoliberal Multiculturalism: Complicities and Implications for Applied Linguistics, Kubota proposes a more critical look at neoliberal aspects of the multilingual turn in applied linguistics that, in celebrating individual difference, challenge its status as a transformative discourse. In her argument from paradigm replacement, Kubota posits that because the multilingual turn, to some extent, emerges from the principle of individual accountability in a neoliberal political economy, its discourse must be complicit with the aims of a neoliberal agenda. This paper is a reply to some of the issues she raises in that critique. My argument is two-pronged. First, I take issue with the epistemic characterization of individual accountability as the only source of multilingualism within a neoliberal discourse. Second, I challenge her rejection of a democratic cosmopolitanism as a self-determining antidote to the neoliberal ideal (c.f. Calhoun 2002). This paper concludes that an alternate epistemic source of the multilingual turn unites language speakers in more moral and less economic terms, thereby destabilizing the argument from paradigm replacement.